2007
DOI: 10.1002/ccd.21008
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mitral balloon valvotomy

Abstract: Percutaneous mitral balloon valvotomy (PMBV) was introduced in 1984 by Inoue who developed the procedure as a logical extension of surgical closed commissurotomy. Since then, PMBV has emerged as the treatment of choice for severe pliable rheumatic mitral stenosis (MS). With increasing experience and better selection of patient, the immediate results of the procedure have improved and the rate of complications declined. When the reported complications of PMBV are viewed in aggregate, complications occur at appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 70 publications
1
23
1
2
Order By: Relevance
“…17 Fawzy has demonstrated regression of significant TR after successful BMV in young patients with severe MS and significant PH. 18 On the other hand; Sagie et al have found no regression of TR in relatively older patients with mild PH. 19…”
Section: Echocardiography In Assessment Of Results and Follow Upmentioning
confidence: 99%
“…17 Fawzy has demonstrated regression of significant TR after successful BMV in young patients with severe MS and significant PH. 18 On the other hand; Sagie et al have found no regression of TR in relatively older patients with mild PH. 19…”
Section: Echocardiography In Assessment Of Results and Follow Upmentioning
confidence: 99%
“…Mitral stenosis is a progressive disease that leads to heart failure and is finally fatal unless mechanical intervention enlarges the mitral valve orifice to permit adequate cardiac output at a tolerable left atrial pressure. 2 Over the past two decades PTMC has become an acceptedalternative to surgery in the treatment ofpatients with mitral stenosis. Previous studies have confirmed that this procedure is highly successful with a low complication rate and significant short-and long-term improvement in both hemodynamics and patient symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Previous studies have confirmed that this procedure is highly successful with a low complication rate and significant short and long term improvement in both haemodynamic and patients symptoms. 12 Short term improvement in mitral valve area (MVA) and symptoms may occur even when commissures are not split and it may be attributed to other mechanism, such as improvement of leaflets mobility secondary to disruption of the diseased submitral tissue. 13 Evaluation of factors those determine the extent of valve leaflets mobility or excursion is necessary to predict haemodynamic changes with improved mitral leaflets excursion and outcome of PTMC.…”
mentioning
confidence: 99%
“…Successful PTMC was defined as post valvuloplasty valve area > 1.5 cm2 or >50% increase in the mitral valve area without significant complications. 12 …”
Section: Methodsmentioning
confidence: 99%